Approaches to therapy Amlodipine/Indapamide/Perindopril therapy of high arterial hypertension in ischemic heart disease patients with chronic kidney disease stage 1-3 after coronary stenting - Sergey A. Pribylov; Kristina O. Leonidova; Vladislav S. Pribylov; Evgenia V. Gavrilyuk; Nadezhda N. Pribylova (Belgorod National Research University, 2024)
Introduction: Acute coronary syndrome, chronic forms of ischemic heart disease (IHD) and postinfarction cardiosclerosis are the main causes of morbidity and mortality in the world, including Russia. In the XXI century, there is an increase in comorbid pathology, especially in the combination of IHD with arterial hypertension, diabetes, chronic obstructive pulmonary disease and chronic kidney disease. Patients with IHD and chronic kidney disease have a higher incidence of coronary events and complications. The frequency of coronary events and complications indicates the need to improve the diagnosis and treatment of this group of patients. diagnosis and treatment of this group of patients. The aim of the study was to analyze the dynamics of vascular stiffness, pulmonary hypertension (PH), diastolic heart dysfunction and endothelial dysfunction indices in patients with different variants of ischemic heart disease combined with chronic kidney disease (CKD) stage 1-3 using complex therapy of combined hypotensive drug Amlodipine/Indapamide/Perindopril three months after coronary stenting and to compare them with the group of patients on conservative therapy only. Materials and Methods: 85 patients with different forms of IHD, arterial hypertension (AH) on the background of CKD 1-3 stages, as well as data of 42 patients with IHD, AH without renal pathology were analyzed. The first group - IHD, postinfarction cardiosclerosis, CKD stage 1-3 (33 patients); the second group - acute coronary syndrome with ST-segment elevation, Myocardial infarction (MI) (30 patients); the third group - ACS without ST-segment elevation, Unstable angina (UA) (22 patients). Results: The highest indices of vascular stiffness (Pulse wave velocity (PWV), Augmentation index (AI), CAVI, Central Systolic Blood Pressure (SBPao), central arterial pulse pressure (PP)) were registered in combination of ACS with ST-segment elevation and CKD 1-3 stages. These indices are markers of IHD progression in these patients; they also have increased pulmonary hypertension and diastolic dysfunction of the heart, endothelial dysfunction with vasodilation insufficiency in 88% of cases, which even without hemodynamically significant coronary artery stenoses according to coronary CT angiography data leads to the development of ACS with ST-segment elevation and ACS without ST-segment elevation with MI. Amlodipine/Indapamide/Perindopril was prescribed to all patients due to high arterial hypertension on admission against the background of basic therapy of IHD and coronary stenting. Coronary CT angiography in patients with comorbid renal pathology does not lead to aggravation of chronic kidney disease after 3 months, on the contrary; in this group of patients the most pronounced decrease of arterial stiffness (AS), AI, SBPao, PP with elevation of glomerular filtration rate (GFR) and decrease of creatinine in blood occurs in comparison with the group of patients who did not undergo coronary stenting, they were only on conservative therapy. Conclusion: Prescription of three component drug Amlodipine/Indapamide/Perindopril on the background of baseline therapy especially in combination with surgical vascularization of the heart is justified.